A Multicentre UK Study of Outcomes for Locally Advanced Sinonasal Squamous Cell Carcinoma Treated with Adjuvant or Definitive Intensity-modulated Radiotherapy. Issue 10 (October 2021) - Slevin, F.; Pan, S.; Mistry, H.; Denholm, M.; Shor, D.; Oong, Z.; Price, J.; Jadon, R.; Fleming, J.C.; Barnett, G.; Dixon, L.; Prestwich, R.; et al.
Abstract: Aims: Sinonasal malignancies are rare; the most common histological subtype is squamous cell carcinoma (SCC). No randomised trial data exist to guide treatment decisions, with options including surgery, radiotherapy and chemotherapy. The role and sequence of a primary non-surgical approach in this disease remains uncertain. The aim of this study was to present treatment outcomes for a multicentre population of patients with locally advanced, stage IVa/b sinonasal SCC treated with radical-intent intensity-modulated radiotherapy, either definitively or postoperatively. Materials and methods: Consecutively treated patients with locally advanced, stage IVa/b sinonasal SCC at four UK oncology centres between January 2012 and December 2017 were retrospectively identified. Descriptive statistics and survival analyses were carried out. Univariable Cox regression analysis was carried out to evaluate the relationship between patient, disease and treatment factors and survival outcomes. Results: In total, 56 patients with sinonasal SCC were included (70% maxillary sinus, 21% nasal cavity, 9% ethmoid/frontal sinus). Forty-one patients (73%) were treated by surgery/adjuvant (chemo)radiotherapy and 15 (27%) by definitive (chemo)radiotherapy. The median duration of follow-up was 3.8 years (interquartile range 2.0–4.7 years). Estimates for 5-year overall survival and progression-free survival were 30.2% and 24.2%, respectively. Local, regional and distant treatment failures were seen in 33%, 33% and 16% of patients, respectively. Univariable analysis revealed inferior progression-free survival for patients treated with neck dissection (hazard ratio 2.6, 95% confidence interval 1.2–6.1, P = 0.022) but no other significant association between the studied factors and survival outcomes. Conclusion: We show poor survival outcomes and high rates of locoregional treatment failure for patients with locally advanced stage IVa/b sinonasal SCC. There is a need to investigate improved treatments for this group of patients. Highlights: Multicentre UK treatment outcomes for locally advanced stage IV sinonasal squamous cell carcinoma. Poor survival and high rates of local failure. Considerable variation in treatment approach.